2003
DOI: 10.1068/p5037
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Modulation of Self-Motion Perception

Abstract: Attentional effects on self-motion perception (vection) were examined by using a large display in which vertical stripes containing upward or downward moving dots were interleaved to balance the total motion energy for the two directions. The dots moving in the same direction had the same colour, and subjects were asked to attend to one of the two colours. Vection was perceived in the direction opposite to that of non-attended motion. This indicates that non-attended visual motion dominates vection. The attent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 16 publications
4
43
2
Order By: Relevance
“…Kitazaki and Sato (2003) produced a vection stimulus consisting of red dots moving upward and green dots moving downward. They reported that when participants attended to the red or green dots, the unattended dots' motion was the dominant stimulus component involved in inducing vection.…”
Section: Introductionmentioning
confidence: 99%
“…Kitazaki and Sato (2003) produced a vection stimulus consisting of red dots moving upward and green dots moving downward. They reported that when participants attended to the red or green dots, the unattended dots' motion was the dominant stimulus component involved in inducing vection.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is called vection (Fischer & Kornmuller, 1930). Several stimulus attributes are known to af-f f fect the subjective strength or direction of vection, such as depth (e.g., Ito & Shibata, 2005), visual area (e.g., Brandt, Dichgans, & Koenig, 1973), motion direction (e.g., Seno & Sato, 2009), and attention (e.g., Kitazaki & Sato, 2003). To date, color is one of the stimulus attributes in vection induction that has rarely been tested.…”
mentioning
confidence: 99%
“…As our visual system readily organizes visual stimuli into figure versus ground (i.e., perceptual objects versus background), the findings by Ohmi et al (1987) could be interpreted as the perceived background dominating vection, whereas "figures" (e.g., objects in the foreground) having less, if any, effect on vection (Kitazaki & Sato, 2003;Ohmi et al, 1987). This hypothesis was confirmed and extended in a clever series of experiments by Seno et al (2009), who used two independently moving luminance-defined gratings organized to form perceptually bistable displays like a Rubin's vase that show spontaneous reversals of the figure-ground (i.e., the object-background) relationship.…”
Section: Importance Of Perceived Object-background Relation For Vectionmentioning
confidence: 99%
“…In particular, many factors that have been shown to facilitate vection are also typical properties of the perceived background, like occupying a large field of view, peripheral stimulation, lower spatial frequencies, rigidity and coherent visual motion, being a ground plane, being unattended, or being further away than other parts of the display. For example, paying particular attention to one of the two motion components in Kitazaki & Sato (2003) might have emphasized it's "object" or "foreground" status, such that other aspects of the stimulus were more likely to be perceived as a background and thus dominated vection. Similarly, fixating a stationary part of the display might have perceptually enhanced its objectlikelihood, such that the other (now "background") stimulus dominated vection.…”
Section: Importance Of Perceived Object-background Relation For Vectionmentioning
confidence: 99%
See 1 more Smart Citation